Bibliometric Analysis of Artificial Intelligence Integration in English as a Foreign Language Education: Trends and Patterns - Muslimin, Afif Ikhwanul (Universitas PGRI Adi Buana Surabaya, 2024)
This research presents a comprehensive bibliometric analysis of the integration of artificial intelligence (AI) in English as a Foreign Language (EFL) education, focusing on trends, patterns, and implications within the scholarly literature. By examining journal articles published between 2010 and 2024, this study reveals a significant increase in publications on AI integration in EFL education, particularly after 2019, possibly influenced by the shift to online teaching during the COVID-19 pandemic. The analysis identifies China as the most productive country in this field, followed by Taiwan and Saudi Arabia. Furthermore, the study highlights key authors and documents contributing to the discourse, shedding light on the most cited articles and prolific authors. The findings underscore the growing interest and potential of AI in transforming EFL education, offering insights for educators, researchers, policymakers, and technology developers to leverage the transformative power of AI effectively. Recommendations for future research directions and considerations for publishing in relevant journals are also provided. Despite the limitations of relying solely on the Scopus database, this research sets the stage for further exploration of AI integration in EFL education and emphasizes the need for continued investigation and innovation in this evolving field.